Manajemen Berbasis Madrasah (MBM) Perspektif Fungsi Perencanaan Dalam Meningkatkan Partisipasi Orang Tua Bidang Sarana Dan Prasarana Pada MTs Muslimat NU Kota Palangkaraya - Hanafiah; Asmawati; Ajahari; Puspita; Misbah (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2023)
This study aims to describe School-Based Management from the perspective of planning functions for increasing parental participation in facilities and infrastructure at MTs Muslimat NU Palangka Raya. The research approach used is descriptive-qualitative, using the case study method. The subjects of the research were the Head of MTs NU Palangka Raya, the Vice Principal for Curriculum Affairs, the Committee Management, and parents of students. The determination of research subjects was carried out using purposive sampling and data collection techniques through observation, interviews, and documentation. The stages of data analysis were carried out in four stages, namely data collection, data grouping, data presentation, and conclusion. The results showed that the implementation of Madrasah-Based Management in the planning aspect was carried out through program planning meetings at the beginning of the year, which involved all stakeholders in the Islamic school, such as the head of the Islamic school, deputy head of the Islamic school, treasurer, educators, and education staff, including Islamic school committee administrators and student guardians. The aim is to get input and feedback as well as find solutions if there are problems with the program being prepared. The choice of time is also intended so that parental involvement in program planning can be more optimal. Prior to discussion at the meeting forum, the school prepared a draft planning program, including estimates and sources of the required costs. The program draft was made by the school based on the SWOT analysis and translated into the RKAS. The involvement of related parties, including parents of students, in meeting activities is intended to grow parents concern and sense of belonging to the school and improve the quality of the school. Involving various parties in planning and managing activities is one manifestation of the implementation of the MBM function. Apart from going through the annual meeting, the school also conducts socialization strategy programs and development programs by utilizing social media such as WhatsApp groups and year-end meetings when distributing student report cards.